Impact of Delayed Early Antiretroviral Therapy Initiation on Treatment Outcomes in Infant Macaques Exposed to SHIVAD8 - Li Ma; Yoshiaki Nishimura; Xueling Wu; Olivia Donau; Eunice Vincent; Hong Lu; Robert V. Blair; Lara A. Doyle-Meyers; Malcolm Martin; Ronald S. Veazey; Huanbin Xu; Xiaolei Wang (Viruses, 2025)
Infants born to HIV-positive mothers remain at significant risk of HIV acquisition despite maternal adherence to antiretroviral therapy, cesarean delivery, and formula feeding. Our previous study reported that initiating early antiretroviral treatment at three days post-SIV infection resulted in approximately eighty percent of pediatric virologic remission. In this study, we investigated treatment outcomes in postnatally SHIV-exposed infant macaques when early intervention was delayed by two days, as well as the mechanisms underlying virologic control. The results showed that, although initiating treatment at five days post-exposure effectively suppressed viral replication, only one of the three infant macaques achieved a sustained state of virologic remission following analytical treatment interruption. Notably, this virus-controlled infant lacked detectable virus-specific immunity, including neutralizing antibodies, cytotoxic T cell responses, and antibody-dependent cellular cytotoxicity. These findings highlight the critical importance of early treatment initiation as a key determinant of virologic control in HIV-exposed, infected infants. This study provides valuable insights for guiding early pediatric HIV intervention strategies in clinical settings.